Cytokines and Colony Stimulating Factors Methods and Protocols - Körholz, Dieter.; Körholz, Dieter.; Kiess, Wieland.; Kiess, Wieland. (Methods in Molecular Biology,, 2003)
Enormous effort has been spent developing many new laboratory techniques for studying immune cells and the immune system, not only to increase fundamental understanding, but also to procure therapeutic success in a clinical setting. In Cytokines and Colony Stimulating Factors: Methods and Protocols, leading laboratory experts describe for the novice investigator a host of novel technologies and molecular techniques specifically designed to study cellular immunology and promote its gene therapy applications. Presented in step-by-step detail to ensure ready reproducibility, these protocols range from flow cytometric techniques to detect cytokines and growth factors in different specimens, to methods for generating and expanding dendritic cells and hematopoietic progenitors from different origins. Each proven method has been fine-tuned for experimental successs by the investigator who developed it, and includes notes on troubleshooting and avoiding potential pitfalls. Although the protocols require little previous experience, even highly skilled researchers will augment their experimental range with many novel timesaving techniques. Cutting-edge and highly practical, Cytokines and Colony Stimulating Factors: Methods and Protocols provides researchers a carefully evaluated set of powerful tools for successful experimental research on cytokines and their role in gene therapy.